Musculoskeletal conditions in children and adolescents managed in Australian primary care - Henschke, Nicholas; Harrison, Christopher; McKay, Damien; Broderick, Carolyn; Latimer, Jane; Britt, Helena; Maher, Christopher G. (BMC musculoskeletal disorders, 2014)
Primary care settings play a vital role in the early detection and appropriate management of musculoskeletal conditions in paediatric populations. However, little data exist regarding these conditions in a primary care context or on the presentation of specific musculoskeletal disorders in children. The aim of this study was to estimate the caseload and describe typical management of musculoskeletal conditions in children and adolescents presenting to primary care in Australia.
Gesehen am 17.08.2020